Theoretical Problems in the Study of Cypriot Literature - Constantinides, Stephanos (Études helléniques / Hellenic Studies, 2007)
This article focuses on concepts that apply to the study of Cypriot literature. The author explores the identity of Cyprus's literary output in relation to the Cypriot identity. He suggests a common republican civil identity for all Cypriots which could embrace the island's Greek and Turkish literatures. He also argues that Cypriot literature could only be in Greek, and considers it as part of the neohellenic literature.